Efficiency of surface plasmon excitation at the photonic crystal – metal interface. (November 2015) - Kuznetsova, T.I.; Raspopov, N.A.
Abstract: We report the results of a theoretical investigation of light wave transformation in a one-dimensional photonic crystal. The scheme considered comprises an incident wave directed in parallel with layers of the photonic crystal under an assumption that the wave vector is far from a forbidden zone. Expressions for propagating and evanescent electromagnetic waves in a periodic medium of the photonic crystal are obtained. It is found that the transverse structure of the propagating wave comprises a strong constant component and a weak oscillating component with a period determined by that of the photonic crystal. On the contrary, the dependence of evanescent waves on transverse coordinates is presented by a strong oscillating component and a weak constant component. The process of transformation of propagating waves to evanescent waves at a crystal – metal interface is investigated. Parameters of the photonic crystal typical for synthetic opals are used in all numerical simulations. The theoretical approach elaborated yields in an explicit form the dependence of the amplitude of a generated surface wave on the period of the dielectric function modulation in the photonic crystal. The results obtained show that in the conditions close to plasmon resonance the amplitude of the surface wave may be on the order of or even exceed that of the initial incident wave.